2021
DOI: 10.3390/met11050816
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Machinability Assessment of DC53 Steel for Die and Mold Industry through Wire Electric Discharge Machining

Abstract: Recently, DC53 die steel was introduced to the die and mold industry because of its excellent characteristics i.e., very good machinability and better engineering properties. DC53 demonstrates a strong capability to retain a near-net shape profile of the die, which is a very challenging process with materials. To produce complex and accurate die features, the use of the wire electric discharge machining (WEDM) process takes the lead in the manufacturing industry. However, the challenge is to understand the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…Multiobjective optimization is the best way to acquire an optimal combination of parameters for contradictory responses [55]. Desirability is an effective way to simultaneously optimize the responses [56,57].…”
Section: One-step Sustainabilitymentioning
confidence: 99%
“…Multiobjective optimization is the best way to acquire an optimal combination of parameters for contradictory responses [55]. Desirability is an effective way to simultaneously optimize the responses [56,57].…”
Section: One-step Sustainabilitymentioning
confidence: 99%
“…As we mentioned earlier, the dependence of the efficiency of EDM processing on the size of the IEG has an extremum, whose position shifts towards the larger IEG with the increasing concentration of contaminants ɣ. . While it is hypothetically possible to solve the problem of continuously adjusting the IEG to the changing position of the extremum by estimating, with a large degree of uncertainty, the fraction of working pulses, one can use acoustic emission instead [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109]. In earlier studies of the WEDM process, it was found that changes in the energy flows do not affect the position of the spectral maxima of VA signals and, thus, the amplitudefrequency pattern [110].…”
Section: Materials Removal Rate (Mrr) Of the Wedmmentioning
confidence: 99%
“…In the manufacturing realm, there is much significance on dimensions verification in railway, aeronautical, defense, marine, and other sectors. Therefore, the accuracy of tools being used to fabricate many specialized parts is considered vital [14,15]. The tools are required for several mechanical works such as drawing, shaping, stamping, coining, blanking, forging, and general applications.…”
Section: Introductionmentioning
confidence: 99%
“…are certain challenges. However, several researchers have been studying problems concerning accuracy in the past [14]. For instance, copper, brass, aluminum, and graphite were employed to Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation